All Optical Demultiplexer Based on Photonic Crystal Ring Resonators - Serajmohammadi, Somaye; Alipour-Banaei, Hamed; Mehdizadeh, Farhad (Recent Advances in Electrical & Electronic Engineering, 2014)
Improving transmission efficiency, quality factor, channel spacing and crosstalk levels are the top priorities in designing optical demultiplexers, suitable for wavelength division multiplexing applications. In this paper we proposed a novel structure for designing optical demultiplexer based on photonic crystal ring resonator. For performing wavelength selection task, we used two ring resonators. The resonance wavelength of the ring resonators depends on the dimensions of the ring core, therefore we chose two different values for the lattice constant of the ring resonators core section. As a result, our proposed structure is capable of selecting two optical channels with central wavelength equal to 1552.2 nm and 1553.3 nm. The channel spacing is 1.1 nm. The transmission efficiency of both channels is more than 99% and the crosstalk level is better than -11 dB.
Keywords: photonic crystal